Exploring how an intervention-based approach leads to social leadership transformation: A multi-disciplinary case study - Dayaram, Kantha; Tiwari, Reena (Emerald Publishing, 2022)
The importance of leadership capability as a priority graduate attribute in preparing graduates to be globally employable has been noted in prior business and education literature. However, leadership development programs tend to be offered as extracurricular lineups that are available to a limited number of student applicants or self-take ups in student organisations. A more recent reimaging of leadership development has been a focus towards social change capabilities. Social change leadership reconfigures leadership from being a traditional positional leadership to being a wider community-civic engagement leadership. Here we use social change leadership as a way to develop students' leadership capabilities with a focus on (1) enhancing students' self-knowledge, including leadership competence and (2) widening access to facilitate positive social change. This chapter presents the findings from a study that empirically tested social change leadership by embedding its competencies into the curriculum as a way to broaden students' access to leadership development. The study specifically employed an intervention-based methodology comprising social change learning pedagogies and assessments. Data were collected from 152 pre surveys and 84 post surveys in undergraduate and postgraduate business and humanities courses. The results provide support for a co-curricular design that embeds social change leadership competencies across units/courses in a degree program to widen student access and to develop graduate attributes that align with social change and employability.